2016
DOI: 10.1007/s00271-016-0509-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential of precision surface irrigation in the Indus Basin Irrigation System

Abstract: In this research we explore the potential of precision surface irrigation to improve irrigation performance under the warabandi system prevalent in the Indus Basin Irrigation System. Data on field dimensions, field slopes along with characteristic soil infiltration properties and outlet discharge were collected through a survey of a sample tertiary unit of Maira Branch Canal, Khyber Pakhtunkhwa Province, Pakistan. The performance of all fields in the tertiary unit was analysed and reported in aggregate, with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The R 2 and the MAPRE values were 0.56 and 7.7% in the study area, respectively. The results demonstrated that using Equation (13) to estimate FC generated reliable results in the study area. Figure 6.…”
Section: Establishment Of the Normalization Function And Ptf And Verimentioning
confidence: 75%
See 1 more Smart Citation
“…The R 2 and the MAPRE values were 0.56 and 7.7% in the study area, respectively. The results demonstrated that using Equation (13) to estimate FC generated reliable results in the study area. Figure 6.…”
Section: Establishment Of the Normalization Function And Ptf And Verimentioning
confidence: 75%
“…Li and Zhang [10] determined that Manning's roughness values can range from 0.02 to 0.05 with border irrigation. Zhang et al [11], Bautista et al [12], and Anwar et al [13] have reported Manning's roughness values of 0.02-0.40, 0.04-0.10, and 0.04-0.16, respectively. Other published studies have often used a representative value of Manning's roughness to simulate furrow irrigation [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The water losses are deep seepage and runoff, which cannot be avoided, thus the application efficiency of surface irrigation is sometimes low (Amer, 2009).The application efficiency depends upon user-selected required depth of application. So, it is possible to obtain 100 per cent application efficiency by selecting a high required depth of application (Anwar et al, 2016).Despite this progressive water shortage farmers continue to use flooding irrigation. Poor management, uniformity and distribution of water have been cited as the most frequent problems of flooding irrigation, resulting in waterlogging, salinization and less water use efficiency (Ali & Mohammed, 2015).The efficiency with which water is applied under surface irrigation methods is often assessed through predefined performance parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It gives information of water losses through deep percolation and runoff. Although AE has been widely used as a decision criteria, the indicator has been criticized as being subjective to the user choice for the required depth (Anwar et al, 2016), and the possibility of achieving high AE, yet inadequate irrigation performance by applying less than CWR to minimize losses to deep percolation (Irmak et al, 2011). AD provides an estimate of irrigation adequacy (under-irrigation, proper irrigation, overirrigation) to deliver the amount of water required to adequately irrigate crops (Burt et al, 1997).…”
Section: Data and Toolsmentioning
confidence: 99%
“…With limited literature on spate irrigation, field water management was described in terms of water rights and rules, field structures, field distribution systems and size of command area , Komakech et al, 2011, Van Steenbergen, 1997, Koppen et al, 2007. Previous studies on field design and optimization focused on conventional irrigation systems with a fixed predetermined supply and application time (Bautista et al, 2009b, Zerihun et al, 2005, Salahou et al, 2018, Adamala et al, 2014, Anwar et al, 2016, Bo et al, 2012 while research on field design in spate irrigation characterized by water supply variability is uncommon. Moreover, research on optimizing field dimensions and cut-off times (Tco) for a range of unpredictable inflow volumes under the complex conditions encountered in spate irrigation are lacking.…”
Section: Introductionmentioning
confidence: 99%